Budżetowanie przychodów i kosztów w samodzielnym publicznym zakładzie opieki zdrowotnej - Lewicka, Beata (Budgeting Incomes and Expenses in Independent Public Health Care Institution, 2005)
The reform of health care in Poland, the marketing of medical services, the increased competition of medical institutions make independent public health care institution managers search for new ways of executing these subjects. In the article, budgeting was presented as a managment tool that helps running an independent public health care institution more effectively. There were also rules pointed out of how to separate and divide liability centres for expenses and profits centres and ways to impute incomes and expenses in creating budgets as business plans.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 276-285